Broadband VHF maritime communications based on cognitive radio - Bolas, Eduardo José Ludovico (2016)
Traditionally, maritime business is associated to transportation, which represents about 90% of global trade, and fishery, but new activities at sea, opened up by technological innovations, are transforming economical context of maritime services and resources. In the future, the massive use of technology to support endurance and ranging of maritime operations, namely in intelligent transport systems and autonomous vehicles areas, would lead to federations of maritime based embedded computing devices. Nevertheless, existing systems are not prepared to support such paradigm change. Currently, stovepiped systems rely on narrowband communications systems, where voice and low data rate are the most common used services, and specific broadband applications, such as Internet access, are supported by satellite communications (SATCOM). Unfortunately, UMTS/LTE networks do not provide consistent solutions, due their limited sea coverage, so there is a need for an additional capacity that can provide acceptable performances at low cost, which might act as a complement or even an alternative to satellite. We propose a Cognitive Radio based Broadband VHF (CR-B-VHF) communications solution to provide appropriate connectivity to support current information exchange requirements and enable future developments on maritime services and applications, thus avoiding SATCOM inconveniences. This CR-BVHF network would operate in a context of spectrum scarcity, within hierarchical spectrum access model, and use cognitive radio based concepts to implement a dynamic system that can activate and deactivated subcarriers, according to spectrum opportunities, ensuring an adequate interference level at incumbent's live services. The main contribution of this thesis work is the proposed CR-B-VHF framework and the demonstration of its suitability, feasibility and deployability. The presented relevancy analysis provides an overview of the state of the art on maritime business and its associated support communications and information systems, and prospects future requirements and applications for low-cost broadband access. The developed solutions for detection and exploitation of multiple non-contiguous narrowband spectrum opportunities in maritime VHF band, within a hierarchical spectrum access context, and their envisage performances, provide good indications regarding attainability of opportunistic BVHF systems and their future deployment. Finally, the discussion on regulatory and standardization issues intend to contribute for a shared problem solving, providing an end user perspective of hierarchical spectrum access. Despite the fact that technical aspects are nor the main issues on opportunistic systems deployment, novel proposed Spectrum Coherences Detector and its experimental demonstrated performances might be an important enabler and an additional argument to convince maritime communications stakeholders.